Bhōjarājīyamu : vacanamu - Kuppusvāmayya, Nāgapūḍi (SAMP early 20th-century Indian books project, 1927)
Adaptation of Bhōjarājīyamu, Telugu poem about Bhojaraja, King of Malwa, 11th cent., by Anantāmātyuḍu, 15th century Telugu poet.